2016
DOI: 10.1371/journal.pone.0151676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Road Network Pattern Considering Population Distribution and Central Business District

Abstract: This paper proposes a road network growing model with the consideration of population distribution and central business district (CBD) attraction. In the model, the relative neighborhood graph (RNG) is introduced as the connection mechanism to capture the characteristics of road network topology. The simulation experiment is set up to illustrate the effects of population distribution and CBD attraction on the characteristics of road network. Moreover, several topological attributes of road network is evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The VISSIM parameters need to be calibrated and validated with the investigation data to ensure that the simulation is accurate [54, 55]. Traffic data, capacity and geometric measures were collected during the investigation to calibrate the simulation model in VISSIM [56].…”
Section: Datamentioning
confidence: 99%
“…The VISSIM parameters need to be calibrated and validated with the investigation data to ensure that the simulation is accurate [54, 55]. Traffic data, capacity and geometric measures were collected during the investigation to calibrate the simulation model in VISSIM [56].…”
Section: Datamentioning
confidence: 99%
“…In addition, a research study investigating the correlation between street networks and traffic flow in the city center revealed that urban road traffic networks can be broadly classified into several types, such as square grid, belt, radial, circular radial, and free-form [ 39 , 40 ]. However, the physical road infrastructure is not limited to a single configuration, but often consists of a combination of two or more basic road networks [ 41 43 ]. Accordingly, Syukri et al, utilized Geographic Information Systems (GIS) to determine the spatial availability of transportation in order to reveal the principles that govern road network accessibility [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that the majority of the world’s population is concentrated in low-altitude plains [ 27 ], and the two types of HSI proposed in previous research would be not applicable to study the urban population distribution in such low-altitude areas. Road network density (RND) is an important variable for simulating urban population distribution, as the road grid bureau is the spatial structure of urban population distribution [ 28 ]. Considering the importance of RND in simulating social and economic parameters (such as population and gross domestic product), there are few studies utilizing RND for correction to improve the HSI.…”
Section: Introductionmentioning
confidence: 99%